Bridging the gender digital gap - Judith Mariscal Avilés; Gloria Mayne; Urvashi Aneja; Alina Sorgner (Kiel Institute for the World Economy (IfW), 2018)
Despite the headway the world has experienced over the last couple of years in terms of a substantial increase in digital access; there are still significant challenges to overcome in ensuring women are included in the transformation to a digital society, which in turn will enhance productivity and social development. Efforts to increase internet adoption access through broadband plans and legislative reforms have yielded improvements in use and adoption. However, there is still a stark and pervasive gender inequality in terms of access, ownership of digital devices, digital fluency as well as the capacity to make meaningful use of the access to technology. Even though affordability is a key source of exclusion, there are also significant socio-cultural norms that restrict access for women. This policy brief brings forward the argument that access alone is not enough, women need agency and capacity to leverage access. The authors thus highlight the need to make an assessment of the global gender gap and develop meaningful indicators that contribute to the design and implementation of effective policies that drive adoption. We need effective promotion of women's digital adoption not only from the government but also from the private sector and civil society in order to lead the digital adoption of best practices for women around the world.
Keywords: J16; J24; O30; 330; digital gender gap; digital inclusion; digital skills